The Effect of Service Quality, Facilities, And Image on Patient Satisfaction at the Islamic Hospital Sari Asih Ar Rahmah Tangerang - Mahda Rihhadatul Aisy; Ahyakudin; Najmudin (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to determine whether service quality, facilities, and image partially and simultaneously have a positive and significant effect on patient satisfaction at Sari Asih Ar Rahmah Islamic Hospital. This study uses quantitative research with an explanatory approach. The research sample consisted of 100 outpatients at Sari Asih Ar Rahmah Islamic Hospital, selected using random sampling techniques. Data analysis techniques in this study included instrument testing, classical assumption testing, multiple linear regression analysis, hypothesis testing, and coefficient of determination (R²) analysis using SPSS Ver 27 software. Based on the data analysis results, the partial test (t-test) results show that service quality (X1), facilities (X2), and image (X3) partially have a positive and significant effect on patient satisfaction (Y). The simultaneous test (F test) results show that the calculated F value (31.994) > F table (2.70) with a significance value of 0.000 < 0.05, which means that service quality, facilities, and image simultaneously have a positive and significant effect on patient satisfaction. Keywords: Service Quality, Facilities, Image, Patient Satisfaction